Interlaminar crack onset in co-cured and co-bonded composite joints under mode I cyclic loading - Shiino, Marcos Yutaka [UNESP]; González Ramírez, Francis Mariana; Garpelli, Felipe Parise; Alves da Silveira, Núbia Nale; de Cássia Mendonça Sales, Rita; Donadon, Maurício Vicente (Wiley, 2019)
Composite joints exhibit different behavior in regard to delamination resistance when dealing with fatigue phenomenon. This research work focuses on an investigation to understand the failure mechanisms on the interfacial strength domain for delamination onset in cocured and cobonded joints. The analysis was based on strain energy release rate versus number of cycles plots that were obtained from fatigue tests in mode I with a stress ratio R = 0.1. The analysis encompassed from the microscopic to mesoscopic level obtained from scanning electron microscopic, and the images processed to extract the most relevant fracture patterns. The main difference between the two technologies was the stress concentration at the crack tip in which the cobonded joint presents a fabric carrier that blunts the adhesive layer, then delaying the delamination. This paper provides important information and guidelines to aid designers in the selection of the best composite joint for high-performance structural applications.
Keywords: adhesive; composite joint; delamination; fatigue